Remote crisis intervention and suicide risk management in COVID-19 frontline healthcare workers - Robles, Rebeca; Infante, Sara; Feria, Miriam; Arango, Iván; Tirado, Elsa; Rodríguez-Delgado, Andrés; Miranda, Edgar; Fresán, Ana; Becerra, Claudia; Escamilla, Raul; Madrigal de León, Eduardo Angel (Frontiers in Psychology, 2023)
Introduction Despite the propagation of virtual mental health services for vulnerable groups during COVID-19 pandemic, the implementation and evaluation of remote evidence-based practices (EBP) to manage them in low- and middle-income countries remains scarce. In the current study, we describe and evaluate the implementation process and clinical impact of brief, remote, manualized EBP for crisis intervention and suicide risk management among healthcare workers attending patients with COVID-19 (COVID-19-HCWs) in Mexico. Methods The implementation process comprised community engagement of volunteer mental health specialists, creation of new clinical teams with different disciplines and skills, intervention systematization through manuals and education through 4-h remote training as main strategies. Mexican COVID-19-HCWs who had used a free 24-h helpline rated their pre- and post-intervention emotional distress. Therapists recorded patients’ pre-intervention diagnosis, severity, and suicide risk, the techniques used in each case, and their post-treatment perception of COVID-19-HCWs’ improvement at the end of the intervention. Results All techniques included in the intervention manual were employed at least in one case (n = 51). At the beginning of the intervention, 65.9% of the COVID-19-HCWs were considered moderately ill or worse according to Clinical Global Impression-Severity (CGI-S) scores, whereas at the end, 79.4% of them were perceived as much or very much improved according to CGI-Improvement scores (CGI-I), and their emotional distress had been significantly reduced (p < 0.001). Discussion This prospective study provides evidence that implementation of remote EBP is feasible and useful to reduce emotional distress and suicide risk among COVID-19-HCWs from a middle-income country. However, this study was limited by lack of a control group, improvement ratings provided by therapists and non-anonymous satisfaction ratings.